The effect of conditioned inhibition on the specific Pavlovian-instrumental transfer effect - Alarcón, Daniel; Bonardi, Charlotte (American Psychological Association, 2016)
Four experiments examined the effect of Pavlovian conditioned inhibition on specific Pavlovian-instrumental transfer (PIT) in human participants. The task comprised an instrumental phase in which two responses (R1, R2) were each paired with one of two outcomes (O1, O2: R1-->O1, R2-->O2), and a Pavlovian phase, in which two CSs, CS1 and CS2 each signalled one of the two outcomes (CS1-->O1, CS2-->O2). In Experiments 1-2 a conditioned inhibitor, X, predicted the omission of one of the outcomes (e.g. CS1-->O1, CS1X-->nothing). In a subsequent test, performance of R1 and R2 was examined in the presence of CS1 and CS2. A specific PIT effect was observed: R1 was performed more than R2 during CS1, and R2 more than R1 during CS2. This PIT effect was significantly reduced by the presence of the inhibitor X in Experiment 1, in which the Pavlovian phase followed the instrumental phase, and in Experiment 2 in which it preceded it. No such effect was observed when X was presented in the absence of any expectation of the outcomes during the PIT test (Experiment 3a), or when X was trained as a signal for an alternative outcome (Experiment 3b). These results are consistent with the suggestion that the specific PIT effect occurs through a stimulus-outcome-response (S-O-R) mechanism, according to which the CS evokes a representation of the outcome which in turn elicits the response (e.g. CS1-->O1-->R1). The conditioned inhibitor suppresses performance of the response by suppressing activation of the outcome representation.